Environmental disclosure practices in mining sector companies in Indonesia - Fajarini Sri Wahyuningrum Indah; Oktavilia Shanty; Suryarini Trisni; Wahyudin Agus; Reswari Hasna Pratista Ardhana; Putri Wulandari Marceylla (E3S Web of Conferences)
This study aims to analyze the environmental disclosure practices of mining sector companies in Indonesia. The report also explores the determinants that influence environmental disclosure: profitability, company size, company age, and environmental performance. This research uses a sample of 45 mining sector companies listed on the IDX for 2020-2022. The collected data is analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that environmental disclosure in Indonesia, based on the GRI Standards 2021, remains relatively low. Company size has a positive effect on environmental disclosure, whereas profitability, company age, and environmental performance do not have an impact on environmental disclosure.